Assessment of status of post-recovery patients with COVID-19 infections in Nepal. - Dhimal,Meghnath (2020)
Executive Summary: Introduction COVID-19 is now a pandemic affecting many countries globally. COVID-19 infection is reported both symptomatic and asymptomatic There are numerous symptoms for COVID-19 which are usually mild and begin gradually. Some people become infected but only have very mild symptoms. Around 1 out of every 6 people who get COVID-19 becomes seriously ill and develop difficulty breathing and seek hospitalization. Unaffected people being worried about getting the COVID-19 infections from someone who has recovered may attempt to avoid them, they may also be worried about being stigmatized by the community. Hence, this study explored the post-recovery physical, mental and social health status of COVID-19 recovered patients returning to normalcy. Methods We used mixed method design for this study. Both quantitative and qualitative approaches were mixed to have an in-depth overview of the research question and the objectives set for the COVID19 post recovered patient study. A total of 552 COVID-19 recovered patients for the quantitative study and 25 recovered patients of COVID-19 infections for a qualitative study was taken. Thematic analysis was done for qualitative study and descriptive statistics was done for a quantitative study. Results For the qualitative study, 25 participants were included for IDI, where 14 of them were army/police and others were from different a profession like teacher, farmer, foreign employment, student, government officer. In the Quantitative study, almost 68 and 35 percent were male and female respondents respectively. Most (42.8%) of them were army and police, about 9 percent were healthcare workers, and other almost 49 percent of the participants were involved in different occupations like a driver, teacher, student, foreign employment, labor work, etc. Regarding their travel history, most (44.6%) of them had traveled Inter municipality followed by 29.9 percent who came from abroad. Forty-nine participants traveled within the national boundary and 8 percent of them had interstate travel history followed by 7.4 percent of them who had inter-district travel history. While only 1.3 percent of recovered patients didn't have any travel history. Almost 33 and 22 percent stayed in home isolation and hospital respectively when infected with COVID-19 but 27 percent of the recovered patients did not reveal the place of stay. Smoking and alcohol consumption habit has decreased among participants before and after COVID-19 infection. On physical health status, it is revealed that the majority of the recovered patients could normally do household chores, activities outside the household and financial work accounting 86.6 percent, 87.5 percent and 84.4 percent respectively. But few of them required assistance in carrying out all those activities. A qualitative study revealed the majority of the COVID-19 symptomatic patients experienced a variety of physical symptoms like fever, headache, body pain, fatigue, tiredness, sore throat, cough, loss of taste, loss of smell, sneezing, loss of appetite and difficulty in breathing. while some felt totally fine without any symptoms during the period of the infection. The majority of them had immunity-boosting ayurvedic herbs during the infection and few of the participants entertained themselves doing their preferred activities in hospitals\quarantine center to cope up with the stress. Moreover, not much difference in the daily functional activities in most of the recovered patients have been revealed while few were found doing fewer activities than usual as they were concerned about their health. On the contrary, few recovered patients were not doing any of the daily work, still being conscious of COVID-19 in fear of getting infected again. For social health, quantitative findings revealed more than half (51.7%) of the participant's social health was highly affected. From the IDI, it was found that family members to be major approached sources in providing support during Covid-19. They shared that the response and support from the relatives varied among their relatives. Some received care and support but, the majority of participants did not experience any affection and love from their relatives. In addition, the majority of the participants felt ignorance and misbehave from society. "Relatives used to be afraid of me after hearing I was infected, even some people used to be afraid of having phone calls, after my corona positive report relatives and community people afraid to come in our house.". "My father was so worried. My wife couldn't sleep the whole night thinking about my health." Moreover, From the quantitative findings, the majority of the participants didn't have any kind of mental stress however, there were few participants who responded they had repeated disturbing and unwanted thoughts about COVID-19, trying to avoid information on COVID-19 and had negative thoughts/feelings towards themselves and others accounting 2.4 percent, 3.3 percent and 1.4 percent respectively. In addition, most of them had faced some financial stress followed by work/business stress and general stress at home. COVID infected patients who were asymptomatic didn't experience any emotional change in them but recovered patients who are symptomatic experienced a wide range of symptoms of psychological stress and disorder. Conclusion A majority of COVID-19 recovered patients had a normal health condition after recovery, while few participants had complicated health conditions even after recovery and require assistance for daily activities. The majority of participants did not experience any affection and love from their relatives due to the fear of COVID-19 where they thought they may get affected as well and also get afraid to receive phone calls. It concludes that most of the patients being affected socially by the community people and relatives. Though mental status seems to be normal among the majority of recovered patients, however, some COVID-19 recovered patients have some kind of mental disturbance. It is recommending that there should make a friendly environment at home and an office setting focused on love and affection to able to live a socially and economically productive life.